PENGEMBANGAN SOFTWARE CAFÉ POS SYSTEM - Taufik, Candra (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2017)
Café businesses are generally owned by small entrepreneurs are emerging in Indonesia, and especially big cities like Bandung. 99ers Café require software Point of Sales (POS) to manage their business, especially in serving the demand and supply of foods and beverages so that there are no errors. Besides, it is expected that financial management becomes better and avoid mistakes recording and presentation of daily and monthly reports are required. Software development using prototype methods with object oriented approach intended to facilitate in solving problems for software development. Object-oriented programming language used is C # .Net and uses MySql database. Development activities include: planning, analysis, design, implementation and testing. In the development of the software, the problem is found at the time the software was tested directly by the user. By using object-oriented methods, that problems can be solved in a relatively short time.